Human-induced changes and phyto-geomorphological relationships in the historical ravaneti landscape of the Carrara marble basin (Tuscany, Italy). Issue 4 (21st April 2023) - Gentili, Rodolfo; Alderighi, Linda; Errico, Alessandro; Salvatore, Maria Cristina; Citterio, Sandra; Preti, Federico; Baroni, Carlo
Abstract: Marble has been extracted from the Carrara quarries (Apuan Alps, Italy) for over two millennia. This cultural landscape is characterised by singular landforms called ravaneti, causing environmental problems due to debris flow, thus imperilling human settlements and natural heritage. Geomorphological and vegetation analyses have highlighted that in a decade, vegetation cover greatly increased, indicating potential for passive restoration of dump deposits. The assessment of plant assemblages indicates a decrease in plant richness and endemics, and an increase in wood and alien species. The conservation of historical ravaneti landscape requires weighted restoration actions to reduce geomorphological hazards and preserve native biodiversity.